Determinants of Microfinance adoption, challenges encountered, and principal solutions: An empirical analysis using theory of planned behaviour (Journal of Innovation in Academia, 2025)
This study aims to determine the factors influencing customers' intentions towards microfinance in Kathmandu Valley. The study employs an explanatory research design in conjunction with the Theory of Planned Behavior framework. Primary data from 303 respondents were collected using the KOBO toolbox.  Descriptive and inferential data analysis was carried out using MS-Excel and SMART PLS 4.0. The majority of respondents consisted of married middle-aged women actively engaged in their own business ventures. Common challenges encountered by microfinance customers included high-interest rates, insufficient security, and limited financial knowledge. The principal solutions identified included the establishment of robust microfinance policies, the integration of innovation and new technologies, the provision of financial training, and the facilitation of enhanced loan repayment strategies. The study revealed that, among the three primary factors examined, both subjective norms and perceived behavioral control had a significant impact on customers' intentions to adopt microfinance.